Research of Physico-Chemical Properties of Synthesized Thiocol Oligomer Based on Sodium Polysulphide, Monochlorohydrine and Ammonium Phosphate (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The purpose of this study is the synthesis and study of thiokol oligomer ДКА-4 brand based on sodium tetrasulfide, epichlorohydrin and ammonium phosphate, which is intended for use as a main component Thiokol sealant. To achieve this goal, a thiokol oligomer based on sodium tetrasulfide, epichlorohydrin, and ammonium phosphate was synthesized and investigated, and the optimal conditions for the synthesis of a thiokol oligomer were determined. Research has been carried out on the influence of the molar ratios of the starting substances on the composition and physicochemical properties of the synthesized thiocol oligomer. The optimum polycondensation temperature was taken as 80о-85о С, the reaction time is 1.5-2 hours, as a result, the yield of the target product reaches 93%. As a result of the studies carried out, the thiokol oligomer with the best performance was obtained at a 1: 1: 1 molar ratio of sodium tetrasulfide, epichlorohydrin, and ammonium phosphate, respectively. Based on the results of IR spectroscopy and differential scanning calorimetry, a reaction for the formation of a thiokol oligomer is proposed.